Immunoperoxidase Stain of Measles Antigen in Tissue Culture - Dubois-Dalcq, M. (1973)
A specific electron microscopy staining technique for measles antigen has been developed by using Vero cells infected with a subacute sclerosing panencephalitis (SSPE) measles virus strain and fixed in glutaraldehyde or formaldehyde. Peroxidase-labeled antibody was prepared according to the method of Avrameas (4). Sera from SSPE patients with high measles antibody titer as well as normal human sera with and without measles antibody were used. With both fixatives, specific labeling was obtained on the surface of infected cells, on the budding site, and on complete viral particles. The cell membrane staining sometimes had a patchy distribution in that the reaction was most intense on the surface projections in front of each nucleocapsid. This suggests modification of the cell membrane in association with the nucleocapsids. In contrast, no label was detected on the membranes of the cells during the latent period from penetration through maturation of the virus. In formaldehyde-fixed cultures, cytoplasmic inclusions were stained, and this label was located on the “fuzzy” material around the nucleocapsids. The smooth type of nucleocapsids, mainly seen in the nucleus, were never labeled. These findings suggest that the antigenic nature of the “fuzzy” nucleocapsids in the cytoplasm may be different from that of the “smooth” nucleocapsids. The immunoperoxidase method gives good resolution of viral antigenic sites at high magnifications under electron microscopy and may be of value in studies on the immunopathogenesis of SSPE and other chronic viral infections.